Polarization‐Tunable Perovskite Light‐Emitting Metatransistor. Issue 1 (23rd November 2022) - Klein, Maciej; Wang, Yutao; Tian, Jingyi; Ha, Son Tung; Paniagua‐Domínguez, Ramón; Kuznetsov, Arseniy I.; Adamo, Giorgio; Soci, Cesare
Abstract: Emerging immersive visual communication technologies require light sources with complex functionality for dynamic control of polarization, directivity, wavefront, spectrum, and intensity of light. Currently, this is mostly achieved by free space bulk optic elements, limiting the adoption of these technologies. Flat optics based on artificially structured metasurfaces that operate at the sub‐wavelength scale are a viable solution, however, their integration into electrically driven devices remains challenging. Here, a radically new approach to monolithic integration of a dielectric metasurface into a perovskite light‐emitting transistor is demonstrated. It is shown that nanogratings directly structured on top of the transistor channel yield an 8‐fold increase of electroluminescence intensity and dynamic tunability of polarization. This new light‐emitting metatransistor device concept opens unlimited opportunities for light management strategies based on metasurface design and integration. Abstract : Monolithic integration of a dielectric metasurface into a perovskite light‐emitting transistor is demonstrated. The "metatransistor" shows an 8‐fold enhancement of the electroluminescence compared to the unpatterned device. The combination of pixelated metasurfaces in the active area and electrically switchable recombination zone enables dynamic tunability of the electroluminescence polarization.